Bump-on-tail distributions caused by Alfvénic redistribution of energetic ions. (1st October 2022) - Nabais, F.; Boboc, A.; Calado, R.; Eriksson, J.; Ferreira, J.; Figueiredo, A.; Hawkes, N.; Hellesen, C.; Kiptily, V.; Mantsinen, M.; Rodrigues, P.; Salewski, M.; et al.
Abstract: A series of experiments was performed in the JET tokamak aiming to study the characteristics and eventual effects of beam injected ion populations further accelerated through 2nd harmonic ion cyclotron heating. It was found that the injection of these ions could affect sawtooth stability and that these populations excite toroidicity induced Alfvén eigenmodes (TAEs) in the core of the plasma. More interestingly, measurements of DD beam-plasma neutrons from the TOFOR spectrometer show that these modes caused local bump-on-tail distributions in energy. Numerical simulations performed with the CASTOR-K code found a strong interaction between the core-localized TAEs and ions with energies at which local minima in the energy distribution were measured.